Implementasi Kebjikan Penataan dan Mutasi Guru Pegewai Negeri Sipil di Lingkungan Dinas Pendidikan Kabupaten Halmahera Utara - Amrin Kamaria (Jurnal Ilmiah Wahana Pendidikan, 2021)
The objectives of this study are: (1) to describe the implementation of the policy on structuring and relocating PNS teachers in the education office of North Halmahera Regency, (2) to describe the supporting and inhibiting factors, and (3) to describe the efforts of the education office of North Halmahera Regency in overcoming the obstacles that arise in implementation of the policy of structuring and transferring civil servants at the elementary and junior high school levels. This study uses a qualitative approach with a descriptive method. The subjects in this study included the head of the education office of North Halmahera Regency, the head of the education planning section, and the head of the elementary and junior high school with the object of implementing the policy of structuring and transferring civil servants at the elementary and junior high school levels at the education office of North Halmahera Regency. Data collection techniques used are observation, interviews and documentation. Data analysis used an interactive model, namely the stages of data collection, data reduction, and data presentation. The triangulation used is source triangulation and technique triangulation. The results of the study indicate that the implementation of the PNS teacher structuring and mutation policy includes three stages, namely organization, interpretation, and application. The organizing stage is in the form of a special team from the education office in charge of analyzing the data on teacher needs and submitting it to the service, then from the office which determines the results of the analysis. The supporting factor for implementation is good communication between the education office and schools. The inhibiting factors are teachers and schools who object to the policy. The education office of North Halmahera Regency has made efforts to overcome the obstacles that arise, namely by making regulations aimed at schools regarding the appointment of honorary teachers.